2019
DOI: 10.1177/0021998319861142
|View full text |Cite
|
Sign up to set email alerts
|

Static and fatigue behaviors of short glass fiber–reinforced polypropylene composites aged in a wet environment

Abstract: In this paper, a new experimental study of the bending static and fatigue behaviors of a composite material reinforced with 40% by mass of short glass fibers (type E) and polypropylene matrix is presented. The composite material is obtained in the form of plates by an injection process, which inevitably affects the distribution of the fibers and therefore the behavior of the material studied. To do this, several techniques are implemented on specimens by cutting them in transverse and longitudinal directions. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…These curves present the typical behavior of the law of Fick for moisture absorption in polymers. 35 The image shows that the HFRP samples absorb 1.56% of water while the GFRP 0.78% and the CFRP 0.86% in the saturation stage. That is, HFRP samples absorb approximately 100% more water than the other laminates.…”
Section: Resultsmentioning
confidence: 99%
“…These curves present the typical behavior of the law of Fick for moisture absorption in polymers. 35 The image shows that the HFRP samples absorb 1.56% of water while the GFRP 0.78% and the CFRP 0.86% in the saturation stage. That is, HFRP samples absorb approximately 100% more water than the other laminates.…”
Section: Resultsmentioning
confidence: 99%
“…Sieberer et al have shown [79] the possibility of approximating the data on stiffness reduction and fatigue damage accumulation in a reference sample on real products. Mansouri et al have used stiffness reduction of SFRPs to investigate the fatigue damage kinetics, combining it with both macroscopic observation of cracks and microscopic examination of interfaces to determine damage mechanisms [80]. Table 3 presents some summarized data on stiffness reduction measurement methods for the fatigue assessment, the informative parameters, and the compositions of the examined SFRPs.…”
Section: Visualization Of Surface Damagesmentioning
confidence: 99%
“…POM is frequently used in metal-plastic joints; for example, safety-relevant elements for chassis ball joints are made from POM. POM and other thermoplastics are frequently used as matrix materials in composites reinforced by short fibers [2][3][4].…”
Section: Introductionmentioning
confidence: 99%